Anti-trypanosomal effects ofAzadiracta indica(neem)extract onTrypanosoma brucei rhodesiense-infected mice - Ngure, Raphael M; Ongeri, Bosire; Karori, Stephen M.; Wachira, William; Maathai, Ronald G.; Kibugi, J. K.; Wachira, Francis N. (Eastern Journal of Medicine, 2009)
Anin vivostudy was carried out to determine the anti-typanosomal effect of aqueous extracts of the barkofAzadiracta indica(neem) inTrypanosoma brucei rhodesiense-infected mice. The extracts were orallyadministeredad libitumtwenty four hours post-infection for three days to mice after dose determination andtoxicity testing. The effect of the extracts in trypanosome-infected mice was monitored for 20 days by determiningchanges in the packed cell volume (PCV), parasitemia levels and survival rate. The bark extracts of the neem plant did not show any acute toxicity to the uninfected animals because no significant effect on weight and PCV was recorded. However, infection withT. b. rhodesienseled to a decrease in weight and PCV, the decrease being morein those animals that were given water only and low doses of plant extracts. The extracts produced a dose-dependent effect at delaying onset of parasites appearance in circulation, decreasing level of parasitemia and PCV.Treatment with 1000 mg/kg of plant extract was comparable to and in some cases more effective than suramin, aknown trypanocidal drug.
Keywords: Azadiracta indica; Trypanosomosis; Parasitemia; Packed cell volume; Survival rate